Immunoglobulin G4 (IgG4)-related disease. A review of head and neck manifestations - Agaimy, A.; Ihrler, S. (Pathologe, 2014)
Immunoglobulin G4 (IgG4)-related disease (also known as hyper-IgG4 disease) is a recently defined emerging condition with highly heterogeneous clinicopathological features and variable disease manifestations. This disorder is characterized by unifocal or multifocal (multiorgan) involvement by tumefactive plasma cell-rich inflammatory infiltrates associated with prominent fibrosclerosis. This not uncommonly interferes with organ function resulting in diverse clinical symptoms. The autoimmune pancreatitis represents the prototype of this disease; however, to date almost all organs have been reported to be involved in this disorder. In the head and neck area several presentations of this disease may be encountered in salivary glands, lacrimal glands, thyroid gland, lymph nodes, soft tissue of the neck, ear and sinonasal tract. However, IgG4 positive plasma cells are occasionally prominent in non-specific chronic inflammatory conditions of the head and neck and the oral cavity unrelated to autoimmune diseases or systemic disorders, thus representing diagnostic pitfalls. The diagnosis of IgG4-related disease should be based on a combination of typical histological, clinical and serological findings.
EVALuna2:6580